Regulators of the secretory pathway have distinct inputs into single-celled branching morphogenesis and seamless tube formation in the Drosophila trachea. - Bourne, C.M.; Lai, D.C.; Schottenfeld-Roames, J. (Developmental Biology, 2022)
Biological tubes serve as conduits through which gas, nutrients and other important fluids are delivered to tissues. Most biological tubes consist of multiple cells connected by epithelial junctions. Unlike these multicellular tubes, seamless tubes are unicellular and lack junctions. Seamless tubes are present in various organ systems, including the vertebrate vasculature, C.elegans excretory system, and Drosophila tracheal system. The Drosophila tracheal system is a network of air-filled tubes that delivers oxygen to all tissues. Specialized cells within the tracheal system, called terminal cells, branch extensively and form seamless tubes. Terminal tracheal tubes are polarized; the lumenal membrane has apical identity whereas the outer membrane exhibits basal characteristics. Although various aspects of membrane trafficking have been implicated in terminal cell morphogenesis, the precise secretory pathway requirements for basal and apical membrane growth have yet to be elucidated. In the present study, we demonstrate that anterograde trafficking, retrograde trafficking and Golgi-to-plasma membrane vesicle fusion are each required for the complex branched architecture of the terminal cell, but their inputs during seamless lumen formation are more varied. The COPII subunit, Sec31, and ER exit site protein, Sec16, are critical for subcellular tube architecture, whereas the SNARE proteins Syntaxin 5, Syntaxin 1 and Syntaxin 18 are more generally required for seamless tube growth and maintenance. These data suggest that distinct components of the secretory pathway have differential contributions to basal and apical membrane growth and maintenance during terminal cell morphogenesis.